O latifúndio no Rio Grande do Sul: velhas formas na funcionalidade de novos atores econômicos na microrregião geográfica da Campanha Central - Rodrigues, Aline de Lima (2006)
The formation processo of the latifundium in Rio Grande do Sul is directly related to the history of occupation and settlement of the space gaucho. It is highlighted that it was through the sesmarias that the latifundia appeared, that were lands distributed unequally, always in favor of detainers of great incomes, contributing to the earth concentration. The latifundium resisted economically and politically while the extensive livestock represented the base of the State s economy with the charqueadas and, later, with the freezing companies. However, with the decadence of that economical segment, because of the prices conjunctures and commercialization unfavorable to the livestock in Rio Grande do Sul, the latifundium has it gradual economical decadence, but it doesn´t decrease in earth concentration, at most, this segment incorporates more capital to earth through the practice of the lease to the managerial farming. This way, this present research has as central concern analyzing the formation process and the factors that allowed the permanence of latifundium in Geographical Microregion of the Campanha Central, that includes the districts of Rosário do Sul, Santa Margarida do Sul, Santana do Livramento e São Gabriel, front to the consolidation of new interests in the Rio Grande do Sul economy. Specifically, the research aimed at: (a) characterizing the process of formation of the latifundium in Rio Grande do Sul; (b) verifying the role of the latifundium, front to the consolidation of the new economical conjunctures, and also identifying is respective exploration form, in the four territorial units that compose MRG of the Campanha Central and, (c) establishing the factors that allowed the performanence of latifundium, in the Geographical Microregion of the Campanha Central, and the perspectives for this cut space front to the new economical factors. In what is referred to the investigative process, the work was divided in fundamental phases for the development of the thematic. Firstly, we tried to accomplish a wide bibliographical revision in seeking for theoretical subsidies on the proposed problem. Later, the research turned to the data collection in primary sources (fieldwork) and secondary through statistical data (IBGE and FEE). The field research based on two different instruments, addressed the representatives of the offices of EMATER in the municipal districts of the MRG and, to the municipal agriculture secretaries. The final phase was constituted in the analysis and interpretation of the data obtained during the fieldwork, the bibliographical research and the research in the statistical organs. As obtained results, it is observed that the current social economic transformations are originating new formas of economical appropriation of latifundia in MRG of the Campanha Central. Latifundia are not anymore, at least not exclusively, explored with the extensive livestock, because through the leases, the great properties the managerial farming of rice and soy penetrate. It is also highlighted that more recently, due to the sales of lands for the accomplishment of the forestation, the great properties watch the insert of the eucalyptus planting and pinus, is areas, previously occupied, only with the extensive creation of cattle. However, that spreading in relation to the economical use of the latifundia is still insufficient to determine a significant change in the agrarian structure, because the leases and the development form in great areas of forest activity contribute to the maintenance of the earth concentration.